Crosstalk between cholesterol metabolism and psoriatic inflammation - Luo, Lingling; Guo, Youming; Chen, Lihao; Zhu, Jing; Li, Chengrang (Frontiers in Immunology, 2023)
Psoriasis is a chronic autoinflammatory skin disease associated with multiple comorbidities, with a prevalence ranging from 2 to 3% in the general population. Decades of preclinical and clinical studies have revealed that alterations in cholesterol and lipid metabolism are strongly associated with psoriasis. Cytokines (tumor necrosis factor-α (TNF-α), interleukin (IL)-17), which are important in the pathogenesis of psoriasis, have been shown to affect cholesterol and lipid metabolism. Cholesterol metabolites and metabolic enzymes, on the other hand, influence not only the biofunction of keratinocytes (a primary type of cell in the epidermis) in psoriasis, but also the immune response and inflammation. However, the relationship between cholesterol metabolism and psoriasis has not been thoroughly reviewed. This review mainly focuses on cholesterol metabolism disturbances in psoriasis and their crosstalk with psoriatic inflammation.